KIT (CD117) Expression in a Subset of Non-Small Cell Lung Carcinoma (NSCLC) Patients - Donnenberg, Albert D. (Public Library of Science, 2012)
We have previously described the expression of CD44, CD90, CD117 and CD133 in NSCLC tumors, adjacent normal lung, and malignant pleural effusions (MPE). Here we describe the unique subset of tumors expressing CD117 (KIT), a potential therapeutic target. Tumor and adjacent tissue were collected from 58 patients. Six MPE were obtained before therapy. Tissue was paraffin embedded for immunofluorescent microscopy, disaggregated and stained for flow cytometry or cryopreserved for later culture. The effect of imatinib on CD117(high)/KIT+ tumors was determined on first passage cells; absolute cell counts and flow cytometry were readouts for drug sensitivity of cell subsets. Primary tumors divided into KIT(neg) and KIT(+) by immunofluorescence. By more sensitive flow cytometric analysis, CD117+ cytokeratin+ cells were detected in all tissues (1.1% of cytokeratin+ cells in normal lung, 1.29% in KIT “negative” tumors, 40.7% in KIT(+) tumors, and 0.4% in MPE). In KIT(+)/CD117(high), but not KIT(+)/CD117(low) tumors, CD117 was overexpressed 3.1-fold compared to normal lung. Primary cultures of CD117(high) tumors were sensitive to imatinib (5 µM) in short term culture. We conclude that NSCLC tumors divide into CD117(low) and CD117(high). Overexpression of CD117 in CD117(high) NSCLC supports exploring KIT as a therapeutic target in this subset of patients.